Tlr7 drives sex- and tissue-dependent effects in Sjögren’s disease - Punnanitinont, Achamaporn; Biswas, Sheta; Kasperek, Eileen M.; Osinski, Jason; Zhu, Chengsong; Miecznikowski, Jeffrey C.; Romano, Rose-Anne; Kramer, Jill M. (Frontiers in Cell and Developmental Biology, 2024)
Primary Sjögren’s disease (pSD) is a systemic autoimmune disease that has the strongest female predilection of all autoimmune diseases. The underlying mechanisms that govern this sexual dimorphism, however, remain poorly understood. We hypothesized that pSD females would exhibit more robust disease as compared to males, and that Tlr7 controls distinct disease manifestations in males and females. Using a well-established pSD mouse model, we harvested exocrine glands, and pulmonary and renal tissue from males and females and quantified the inflammation present. We then collected salivary glands, spleens, and cervical lymph nodes and performed flow cytometry to assess immune populations implicated in disease. We also harvested sera to examine total and autoreactive antibodies. Our data revealed that pSD mice displayed sex-biased disease, as pSD females showed decreased dacryoadenitis, but increased nephritis as compared to males. Moreover, females exhibited increased proportions of germinal center B cells and CD4+ activated/memory T cells in the periphery. Additionally, salivary gland immune populations were altered in a sex-dependent manner in pSD. Females with pSD also displayed elevated total and autoreactive IgG as compared to males. Additionally, splenic B cell Tlr7 expression was increased in females. We next generated pSD mice that lacked Tlr7 systemically and found that ablation of Tlr7 was primarily protective in pSD females, while Tlr7-deficient pSD males showed heightened disease. Thus, pSD mice display sex-biased disease and these dichotomous manifestations are governed by Tlr7 activation. This study identifies Tlr7 as a druggable target for pSD, and highlights the importance of studying pSD disease mechanisms in both sexes.